DSD Due to 5α-Reductase 2 Deficiency - from Diagnosis to Long Term Outcome - Costa, Elaine M.F.; Domenice, Sorahia; Sircili, Maria Helena; Inacio, Marlene; Mendonca, Berenice B. (Seminars in Reproductive Medicine, 2012)
Most of the patients with 5α-RD 2 deficiency are reared in the female social sex due to their severely undervirilized external genitalia but ~60% who have not been submitted to orchiectomy in childhood undergo male social sex change at puberty. In our cohort of 30 cases from 18 families, all subjects were registered in the female social sex except for two children—one who had an affected uncle and the other who was diagnosed before being registered. The majority of the patients were satisfied with the long-term results of their treatment and surprisingly, penile length was not associated with satisfactory or unsatisfactory sexual activity.Steroid 5α-RD2 deficiency should be included in the differential diagnosis of all newborns with 46,XY DSD with normal testosterone production before gender assignment or any surgical intervention because these patients should be considered males at birth.
Keywords: 5α-reductase 2 deficiency; disorders of sexual development; outcome